RESISTENSI TERHADAP PERAN GENDER MASYARAKAT ERA VICTORIA DALAM NOVEL PRIDE AND PREJUDICE KARYA JANE AUSTEN - Wahyuni Wahyuni (Prologue: Journal on Language and Literature, 2018)
ABSTRACTThe purpose of this research is to analyze the resistence to the role ofgender by Elizabeth in the novel Pride and Prejudice, a work of JaneAusten, having a general issu on the limitation of woman’s right.Elizabeth did not have right to choose a husband. She received apressure from her mother to have a rich husband no matter she lovedhim or not. In analyzing this novel, the author used De Witt’sopposition theory (1979) used to analyze woman’s resistence. Thetheory states that consensus have never been fully achieved in acommunity, and those who disagree someday will carry out anopposition performed overtly and secretly.From the discussion of this paper, the author concluded that theopposition performed by Elizabeth opposed the custom applied in thecommunity, and she insisted that woman also has the right to be freein selecting the choice of life, spouse, and determining attitude.Key words : Resistence, Gender Role, De Witt’s opposition theory